2019
DOI: 10.1186/s12916-019-1260-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in access to diagnosis and care in Blantyre, Malawi, identified through enhanced tuberculosis surveillance and spatial analysis

Abstract: BackgroundA sizeable fraction of tuberculosis (TB) cases go undiagnosed. By analysing data from enhanced demographic, microbiological and geospatial surveillance of TB registrations, we aimed to identify modifiable predictors of inequitable access to diagnosis and care.MethodsGovernmental community health workers (CHW) enumerated all households in 315 catchment areas during October–December 2015. From January 2015, government TB Officers routinely implemented enhanced TB surveillance at all public and private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…This funding bias was attributed by Canares [29] to the expenses of transporting healthcare supplies across the island, and in a similar manner, the expense of residents to get to the clinics for the same reasons. MacPherson et al (2019) also showed a geospatial relationship between an increase in TB transmission as there are increases in poorer neighbourhoods that are farther from the TB clinics [30]. We, too, found support for this phenomenon which is known as the 'inverse case law' coined by Hart (1971) in the Lancet [31].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This funding bias was attributed by Canares [29] to the expenses of transporting healthcare supplies across the island, and in a similar manner, the expense of residents to get to the clinics for the same reasons. MacPherson et al (2019) also showed a geospatial relationship between an increase in TB transmission as there are increases in poorer neighbourhoods that are farther from the TB clinics [30]. We, too, found support for this phenomenon which is known as the 'inverse case law' coined by Hart (1971) in the Lancet [31].…”
Section: Discussionsupporting
confidence: 67%
“…MacPherson et al . (2019) also showed a geospatial relationship between an increase in TB transmission as there are increases in poorer neighbourhoods that are farther from the TB clinics [30]. We, too, found support for this phenomenon which is known as the ‘inverse case law’ coined by Hart (1971) in the Lancet [31].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, methods to robustly identify hotspots from routine reporting data would be valuable [15]. However, given that high local rates of tuberculosis notifications may reflect spatially aggregated risk for progression of infection, migration of individuals infected with tuberculosis into the area [16], or spatial heterogeneity in diagnostic capacity [17], finding new ways to probe routine surveillance data to find evidence of local transmission is a priority.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, it was estimated that only 52% of Nipah outbreaks were detected through passive surveillance systems and that the number of missed outbreaks increased with distance from the surveillance hospital [ 30 ]. This finding was supported by MacPherson et al [ 43 ], who found that the TB case notification rate halved for every 3.2–3.5 fold increase in distance from the nearest TB clinic. In a study carried out by Etyang et al [ 44 ], there was a significant decrease in infectious- and parasitic disease related hospital admissions for every 5 km increase in distance from the hospital.…”
Section: Resultsmentioning
confidence: 53%